Optimization Model for the Implementation of Rock Mining Policy Post Law Enactment of the Republic of Indonesia Number 23 the Year 2014: Case Study in Subang Regency, West Java Province - Gede Suyasa; Muchlis Hamdi; Prio Teguh; Megandaru (GoAcademica Research & Publishing, 2019)
The purpose of this study was to find a model for optimizing rock mining licensing in the Subang Regency area after the enactment of the law of the Republic of Indonesia number 23 of 2014. The method used in this study was a qualitative method by interviewing relevant parties and searching literature. The results showed that the implementation of the policy on the issuance of rock mining permits in the Subang regency region after the enactment of the Law of the Republic of Indonesia Number 23 of 2014 was not running optimally, it was influenced by several factors such as the presence of actors consisting of Bureaucracy, Entrepreneurs and Communities having different interests but mutually related to one another in the process of issuing a rock mining permit after the authority to manage the rock mine was carried out by the province of West Java. The optimization model for the issuance of rock mining permits in the Subang Regency of West Java Province can be applied by focusing on the aspects of good and dynamic processes with the principles of governance of the environmental environment on the elements of actors, interests & relations.